Peritoneal tuberculosis with elevated serum CA 125 level mimicking advanced ovarian carcinoma in an adolescent - Corapçioğlu, Funda; Güvenç, B Haluk; Sarper, Nazan; Aydoğan, Ayşen; Akansel, Gür; Arisoy, Emin Sami (The Turkish Journal of Pediatrics, 2006)
Differential diagnosis between tuberculous peritonitis and peritonitis carcinomatosis is extremely difficult in patients with ascites, peritoneal implants and elevated CA 125 level. A 16-year-old girl presented with abdominal distention, intermittent fever and weight loss. Physical examination and radiologic studies revealed massive ascites, generalized peritoneal thickening and slightly enlarged right ovary with a cystic mass and left pleural effusion. Serum CA 125 was 939 U/L (normal range: 0-35 U/L) and other tumor markers including alpha fetoprotein (AFP) and beta-human chorionic gonadotropin (HCG) were within normal range. Acid-fast stain and culture were negative for Mycobacterium tuberculosis. Diagnostic laparoscopy and biopsy were performed with the presumptive diagnosis of peritonitis carcinomatosis, and histologic examination revealed multiple granulomas with epithelioid cells and caseification necrosis which confirmed tuberculosis. Quadruple anti-tuberculosis treatment was administered and the patient’s clinical findings and serum CA 125 level returned to normal. In conclusion, tuberculous peritonitis should be considered in the differential diagnosis of patients with ascites and elevated serum CA 125. This marker may be useful in monitoring treatment response.